Revisão taxonômica dos grupos de espécies Dichotomius (Selenocopris) carbonarius e Dichotomius (Selenocopris) nisus (Coleoptera: Scarabaeidae: Scarabaeinae) - Ferreira, Sheila Cassenote (2022)
The genus Dichotomius Hope, 1838 is endemic to the western hemisphere, widely distributed in the American continent, with species from the United States to Argentina. It currently has about 200 valid species, of which approximately 100 are found in South America. Of the species groups within the Selenocopris subgenus, only the D. carbonarius group with seven described species, some widely distributed and with imprecise original descriptions that make it difficult to identify their species, does not present a taxonomic revision. The general objective of the research was to taxonomically review the Dichotomius (Selenocopris) carbonarius and Dichotomius (Selenocopris) nisus species groups, as well as provide diagnoses for the species already described in the groups, including illustrations and photographs of the specimens and their genitalia; Create a dichotomous key to identify species of the D. carbonarius group; and describe possible new species. The main justification of the study is that the studies conducted with the help of this work will result in taxonomic publications that will be essential for the knowledge and understanding of Neotropical biodiversity. Taxonomy works are important instruments when it comes to practices for the conservation of biodiversity. The study was based on 3,932 dry-preserved specimens, including type specimens of all available names so far assigned to the species groups Dichotomius (Selenocopris) carbonarius and Dichotomius (Selenocopris) nisus. The specimens were donated by curators of several institutions. The D. carbonarius species group now comprises eleven species, some of which are widely distributed: Dichotomius carbonarius (Mannerheim, 1829), Dichotomius cuprinus (Felsche, 1901), Dichotomius glaucus (Harold, 1869) Dichotomius luctuosus (Harold, 1869), Dichotomius lycas (Felsche, 1901), Dichotomius opacus (Blanchard, 1846) status. rev. Dichotomius schmidti sp. nov., Dichotomius dimarei sp. nov., Dichotomius zenaldoi sp. nov., Dichotomius aguilari sp. nov. and Dichotomius jarafaeli sp. nov. Lectotypes are designated for D. carbonarius, D. cuprinus, D. glaucus, D. lycas and D. luctuosus. Dichotomius pseudocuprinus Gandini & Aguilar, 2009 is proposed here as a junior subjective synonym of D. lycas. D. interstitialisis is placed in its own species group. An identification key for the species, diagnostics and distribution maps are provided. The components of the male genitalia of these species are described and illustrated for the first time. In the second chapter, the taxonomic history of the species that Luederwaldt included in the "Nisus" section is reviewed and discussed. The following new synonyms are proposed: Pinotus taunayi (Luederwaldt, 1931) as a subjective synonym of D. geminatus (Arrow, 1913), and Pinotus taunayi pilosus (Luederwaldt, 1931) as a subjective synonym of D. nisus. Lectotypes are designated for D. nisus and Pinotus garbei. D. lycas is placed in the D. carbonarius group. Up-to-date redescriptions, diagnostics, images, and distribution data are provided for D. nisus and D. superbus.